OPERATION SYSTEM DESIGN OF LIQUID BULK TERMINAL, PORT OF BENOA, DENPASAR CITY, BALI PROVINCE - Muzaki Mutawasith, Rizki
Port of Benoa is one of the vital transportation infrastructures for Bali Province. With the establishment of Benoa Port as the Bali Maritime Tourism Hub (BMTH), Port of Benoa needs to develop facilities and infrastructure to support the program. One of the things that needs to be developed to support the development of Benoa Port as the Bali Maritime Tourism Hub (BMTH) is the fulfillment of energy in the form of fuel oil for Denpasar City in particular. In addition to meeting the needs of the program, the development of a Fuel Oil Terminal at Benoa Port is also needed to become a gateway to meet the increasing fuel oil needs of Denpasar residents. Therefore, to be able to facilitate the logistics flow of fuel commodities to meet the needs, this Final Project will discuss the Operation System Design of Liquid Bulk Terminal, Port of Benoa, Denpasar City, Bali Province. The discussion in this Final Project includes the design of operating patterns at the dock, design of operating patterns in the stacking field, calculation of capital costs, and determination of fuel oil cargo handling rates. The design of the operation pattern at the dock includes mooring analysis, planning the type and number of fuel cargo handling tools at the dock, determining the productivity of these tools, calculating the duration of loading and unloading fuel cargo, and calculating the capacity of the dock. The results of the calculation of the design handling capacity at the pier obtained are 7,216,363 m3/year. The design of the operation pattern in the stacking field includes the design of the tank farm area, determination of the type and number of fuel cargo handling equipment in the field, and calculation of the stacking field capacity. The result of the design handling capacity calculation in the stacking field is 8,488,440 m3/year. The calculation of costs and determination of fuel cargo handling rates includes the calculation of total capital costs, the calculation of total expenses and income per year during the payback period, and the calculation of fuel cargo handling rates based on terminal capacity utilization conditions.